Negative plate for lithium battery and lithium ion secondary battery comprising same

By using graphite and silicon-based materials in the negative electrode materials of lithium batteries, combined with carbon nanotubes and ligninsulfonate or humic acid, the problem of insufficient circulation and dispersion of the negative electrode materials is solved, and the performance of lithium batteries is significantly improved.

CN119725356APending Publication Date: 2025-03-28MURATA MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311266444.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The circulation and dispersion of the negative electrode materials of existing lithium battery are poor, resulting in poor battery life and circulation performance.

Method used

Graphite and silicon-based materials are used as negative electrode active substances, and conductive adhesives containing carbon nanotubes and lignin sulfonate or humic acid are used as dispersants to improve the performance of negative electrode materials.

Benefits of technology

The circulation performance of lithium batteries and the dispersion of electrode slurry are significantly improved, and the first discharge capacity, first efficiency and capacity retention rate of the battery after cycling are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725356A_ABST
    Figure CN119725356A_ABST
Patent Text Reader

Abstract

The invention provides a negative plate for a lithium battery and a lithium ion secondary battery comprising the same. The negative electrode plate comprises a negative electrode current collector and a negative electrode material, the negative electrode material comprises a negative electrode active substance, and the negative electrode active substance comprises graphite and a silicon-based material; a conductive agent; a binder, wherein the binder comprises a carbon nano tube; the dispersing agent comprises one or two of lignosulfonate and humic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ions, and in particular, relates to a negative electrode sheet for a lithium battery and a lithium ion secondary battery comprising the negative electrode sheet. Background Art

[0002] Among the negative electrode materials of lithium-ion batteries, graphite mixed with silicon-based materials is an effective method to improve the energy density of lithium-ion batteries. Currently, silicon-based materials on the market can be divided into silicon oxide (disproportionated silicon oxide, amorphous silicon oxide, high first-efficiency silicon oxide) and silicon-carbon materials. Compared with other materials, amorphous silicon oxide materials have the advantages of low price, small expansion, and high capacity, but their cycle performance is poor, so they are not valued by the market. In order to solve the problem of poor cycle performance of such materials, the performance can be improved by adding carbon nanotubes to the slurry, but this method has the risk of poor dispersion of carbon nanotubes and low effective utilization of carbon nanotubes, and requires additional equipment, resulting in increased production costs. In addition, water-based negative electrode sheets are prone to bubbles during the slurry preparation process, resulting in foil exposure and particle agglomeration during coating, which in turn affects the battery life and cycle performance. In order to solve the above problems, patents CN102810662 and CN109301250 solve them by adding alcohols and ethers. Such methods are relatively costly and environmentally unfriendly.

[0003] In view of the above problems, it is necessary to develop a negative electrode sheet for lithium battery and a lithium ion secondary battery comprising the negative electrode sheet, which can improve the cycle performance of lithium ion batteries and the dispersibility of electrode slurry. Summary of the invention

[0004] The main purpose of the present invention is to provide a negative electrode sheet for a lithium battery and a lithium ion secondary battery containing the same, so as to solve the problems of poor cycle performance and dispersibility of negative electrode materials for lithium batteries in the prior art.

[0005] In order to achieve the above-mentioned objectives, the present invention provides, on the one hand, a negative electrode sheet for a lithium battery, comprising a negative electrode current collector and a negative electrode material, wherein the negative electrode material comprises: a negative electrode active substance, wherein the negative electrode active substance comprises graphite and a silicon-based material; a conductive agent; a binder, wherein the binder comprises carbon nanotubes; and a dispersant, wherein the dispersant comprises one or both of lignin sulfonate and humic acid.

[0006] Further, the silicon-based material includes one or both of silicon monoxide and silicon-carbon composite materials, preferably amorphous silicon monoxide.

[0007] Furthermore, the particle size D of silicon oxide 50 1μm <D 50<10μm, of which particles with a diameter of <3μm account for 5%-30%, and the size of the silicon grains in the silicon monoxide is <1nm.

[0008] Further, the graphite is selected from natural graphite, artificial graphite or a mixture thereof; the peak intensity ratio D / G of the D peak to the G peak of the Raman spectrum of the graphite is in the range of 0.04-1, preferably 0.3-0.9; and the graphite has a conductivity of >300s / cm, preferably >400s / cm measured at a pressure of 130MPa according to a four-probe test method.

[0009] Further, the conductive agent includes conductive carbon black, conductive graphite, vapor-grown carbon fiber or a combination of two or more thereof. Preferably, based on the total solid weight of the negative electrode material, the amount of the conductive agent in the negative electrode material is 1%-3% by weight.

[0010] Further, the binder includes polyvinylidene fluoride, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose binder or a combination of two or more thereof, preferably polyacrylic acid binder; preferably, based on the total solid weight of the negative electrode material, the amount of the binder in the negative electrode material is 2%-4% by weight.

[0011] Further, the dispersant comprises lignin sulfonate, preferably sodium lignin sulfonate; preferably, based on the total solid weight of the negative electrode material, the amount of the dispersant in the negative electrode material is 0.2%-3% by weight.

[0012] Furthermore, the viscosity of the adhesive is in the range of 400-30000 mPa.s, preferably 3000-20000 mPa.s.

[0013] Furthermore, based on the mass of the binder, the content of the carbon nanotubes contained in the binder is 0.01%-1%, preferably 0.02%-0.3%.

[0014] Another aspect of the present invention provides a lithium-ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet described above.

[0015] By applying the technical solution of the present invention, by using graphite and silicon-based materials, in combination with a conductive binder and a dispersant including one or both of lignin sulfonate and humic acid, the problems of poor circulation of silicon-based materials and foil exposure and particle agglomeration of aqueous negative electrode slurry can be well solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0017] Figure 1 3 are SEM images of negative electrode materials, wherein the two images on the left are images of an embodiment in which carbon nanotubes are directly added to the negative electrode slurry, and the two images on the right are images of an embodiment in which carbon nanotubes are added to a binder.

[0018] Figure 2 2 are images of negative electrode sheets, wherein the two images on the left are images of an embodiment in which the negative electrode material uses a conventional PAA binder and does not contain lignin sulfonate, and the two images on the right are images of an embodiment in which the negative electrode material uses a conductive PAA binder containing carbon nanotubes and contains sodium lignin sulfonate. DETAILED DESCRIPTION

[0019] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0020] As described in the background art, the negative electrode materials for lithium batteries in the prior art have the problems of poor cycle performance and dispersibility. In order to solve the above technical problems, the present application provides a negative electrode sheet for lithium batteries, including a negative electrode current collector and a negative electrode material, wherein the negative electrode material comprises: a negative electrode active material, wherein the negative electrode active material comprises graphite and a silicon-based material; a conductive agent; a binder, wherein the binder comprises carbon nanotubes; and a dispersant, wherein the dispersant comprises one or both of lignin sulfonate and humic acid.

[0021] In the present invention, graphite and silicon-based materials are used as negative electrode active materials, and a binder containing carbon nanotubes is combined with a lignin sulfonic acid and / or humic acid dispersant with a dispersing function to improve the performance of the hybrid electrode. Silicon-based materials, especially amorphous silicon-oxygen materials, have poor cycle performance due to their poor conductivity and high lithium insertion capacity. In the mixed system of graphite and silicon-based materials, the capacity is greatly related to the type of graphite, binder, conductive agent type, dispersant, etc. It is very necessary to study how to make its performance in the hybrid electrode.

[0022] In the present invention, graphite and silicon-based materials are used as negative electrode active materials. Some silicon-based materials can be distributed between graphite particles, which plays a certain role in inhibiting the expansion of silicon-based materials. Graphite with high conductivity can play a certain role in conductivity, which is conducive to the electrochemical performance of silicon-based materials. The binder containing carbon nanotubes can form a large number of chemical bonds with silicon-based materials, strengthen the connection between particles, and provide more conductive networks. The carbon nanotubes are distributed in the binder, which is convenient for the carbon nanotubes to be distributed on the surface of graphite particles, the surface of silicon-based material particles and between particles at the same time, greatly improving the effective utilization rate of carbon nanotubes, improving the ion and electron transfer rate, and promoting the electrochemical performance of silicon-based materials. The lignin sulfonate or humic acid contained in the dispersant contains functional groups such as carboxyl, hydroxyl and sulfonic acid, has a certain surface activity, is conducive to the dispersion of slurry, and at the same time it can reduce the polarity of the binder, improve the compatibility of graphite, silicon-based materials and adhesives, has a certain defoaming effect, and thus reduces the leakage phenomenon.

[0023] In a preferred embodiment, the silicon-based material includes one or both of silicon oxide and silicon-carbon composite material, preferably amorphous silicon oxide. Using silicon oxide as the silicon-based material is more conducive to obtaining a negative electrode material with good performance.

[0024] In a preferred embodiment, the particle size D of silicon oxide is 50 1μm <D 50 <10μm, of which particles with a diameter of <3μm account for 5%-30%, and the size of the silicon grains in the silicon monoxide is <1nm.

[0025] The inventors have found that the particle size of silicon oxide within the above range can alleviate the expansion of the negative electrode material during battery charging and improve the cycle life of the battery. If the particle size is too large, it will lead to a significant volume effect, exacerbating the expansion of the negative electrode sheet during battery charging. If the particle size is too small, the negative electrode active material particles are not easy to disperse, which will affect the dispersion performance of the slurry and may lead to an increase in battery side reactions.

[0026] In a preferred embodiment, the graphite is selected from natural graphite, artificial graphite or a mixture thereof; the ratio D / G of the peak intensity of the D peak to the G peak of the Raman spectrum of the graphite is in the range of 0.04-1, preferably 0.3-0.9; and the graphite has a conductivity of >300s / cm, preferably >400s / cm, measured at a pressure of 130MPa according to a four-probe test method. The D / G of the graphite refers to the ratio of the peak intensity of the D peak to the G peak of the Raman spectrum of the graphite, wherein the D peak of the Raman spectrum of the graphite is the disordered peak caused by sp2 of the graphite, which originates from the vibration of the crystalline edge of the graphite carbon, at a wavelength of 1360cm -1The G peak of the Raman spectrum of graphite is a typical Raman peak of bulk crystalline graphite, at a wavelength of 1585 cm -1 The graphite with parameters within a specific range is more conducive to obtaining a negative electrode material with good performance.

[0027] In a preferred embodiment, the conductive agent includes conductive carbon black, conductive graphite, vapor-grown carbon fiber, or a combination of two or more thereof, preferably, based on the total solid weight of the negative electrode material, the amount of the conductive agent in the negative electrode material is 1%-3% by weight. Using a specific proportion of conductive agent such as conductive carbon black is more conducive to obtaining a negative electrode material with good performance.

[0028] In a preferred embodiment, the binder comprises polyvinylidene fluoride, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose binder or a combination of two or more thereof, preferably polyacrylic acid binder; preferably, the amount of the binder in the negative electrode material is 2%-4% by weight based on the total solid weight of the negative electrode material. Using a specific proportion of a binder such as polyacrylic acid is more conducive to obtaining a negative electrode material with good performance.

[0029] The dispersant includes one or both of lignin sulfonate and humic acid. In a preferred embodiment, the humic acid includes one or more of fulvic acid, palmitic acid, and black humic acid, preferably fulvic acid. In a preferred embodiment, the dispersant includes lignin sulfonate, preferably sodium lignin sulfonate; preferably, based on the total solid weight of the negative electrode material, the amount of the dispersant in the negative electrode material is 0.2%-3% by weight. Using a specific proportion of dispersant, preferably sodium lignin sulfonate, is more conducive to obtaining a negative electrode material with good performance. Among them, if the dispersant content is too low, it cannot play a good dispersing role; if the dispersant content is too high, it will affect the performance of electrical properties such as battery capacity and cycle performance.

[0030] In a preferred embodiment, the viscosity of the binder is in the range of 400-30000 mPa.s, preferably 3000-20000 mPa.s. The use of a binder with a specific viscosity, such as polyacrylic acid, can ensure that the electrode slurry has no processability problems while the battery electrical performance is better. If the viscosity of the binder is too low, the stability of the slurry will deteriorate, and it will not have a good bonding effect. The pole piece is prone to powder loss, which may cause the battery to short-circuit and have poor cycle performance. If the viscosity of the binder is too high, it will make the slurry difficult to disperse, which will cause particle agglomeration and make it impossible to make pole pieces.

[0031] In a preferred embodiment, the content of carbon nanotubes in the binder is 0.01%-1%, preferably 0.02%-0.3%, based on the mass of the binder. If the content of carbon nanotubes in the binder is too low, the electrical performance of the battery cannot be effectively improved; if the content of carbon nanotubes is too high, the dispersion of carbon nanotubes deteriorates, the improvement of battery performance is limited, but the cost will be greatly increased.

[0032] Another aspect of the present application provides a lithium-ion secondary battery, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet described above.

[0033] The lithium ion secondary battery of the present invention is prepared by the following steps.

[0034] Preparation of negative electrode sheet: The negative electrode active material, conductive agent, binder, dispersant and solvent are stirred to prepare negative electrode slurry. The negative electrode slurry is then coated on the negative electrode collector, dried and stamped to form a negative electrode sheet.

[0035] Preparation of electrolyte: An organic solvent, lithium salt and additives are mixed to prepare an electrolyte.

[0036] Battery assembly: stack the prepared negative electrode sheet, separator, lithium sheet, and battery shell in sequence and inject 100 ml of electrolyte, then seal and assemble into a half-cell.

[0037] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0038] Sodium lignin sulfonate is dissolved in water, amorphous silicon dioxide is added, stirred and mixed evenly, then 50% of the total amount of the binder is added and mixed evenly, conductive carbon black is added and stirred until mixed evenly, then the required amount of graphite and the remaining amount of binder are added, stirred and mixed, and finally water is added to adjust the solid content to a film-drawable state. Among them, the binder used is polyacrylic acid (PAA) binder, and the conductive binder is a binder containing a certain amount of carbon nanotubes in the PAA binder. In some embodiments, the conductive binder is not used but the carbon nanotubes are directly added to the negative electrode slurry, see Table 1. The negative electrode slurry is coated on copper foil, dried and punched, and the prepared negative electrode sheet is placed in a vacuum drying oven and dried for 5 hours before being taken out for battery assembly. The prepared negative electrode sheet, diaphragm, gasket, and battery shell are stacked in sequence and injected with 100 ml of electrolyte, and assembled into a half-cell after sealing. The masses of silicon dioxide, graphite, binder (including conductive binder), and conductive carbon black in the negative electrode sheet are 19g, 76.2g, 3g, and 0.8g, respectively. The graphite used in each example has a D / G of 0.7 and an electrical conductivity of 560 s / cm measured at a pressure of 130 MPa according to a four-probe test method. The particle size D of silicon oxide used in each example 50The viscosity of the binder used in each example, the carbon nanotube content (based on the mass of the binder), and the content of sodium lignin sulfonate (based on the mass of the negative electrode material) are shown in Table 1.

[0039] The first discharge capacity, first efficiency, and capacity retention rate after the cycle of the manufactured battery were tested by the following method. Capacity test: Use a charge and discharge rate of 0.1C to test the battery in the charge and discharge voltage range of 0V-1.5V to obtain the first capacity and first efficiency. Cycle test: Charge the battery at 0.1C current after the capacity test, and then use 1C current for charge and discharge cycle test to test the capacity retention rate after 50 cycles. Charge and discharge cut-off voltage: 0V-1.5V. See Table 1 for the test results.

[0040] Table 1

[0041]

[0042]

[0043] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0044] Comparing Examples 1-2 with Comparative Examples 1-7, it can be seen that the negative electrode sheet for lithium batteries of the present invention has improved slurry dispersibility, first discharge capacity, first efficiency and capacity retention rate after cycles. Specifically, comparing Examples 1-2 with Comparative Examples 1 and 7, it can be seen that when the viscosity of the binder is outside the scope of the present invention, it will result in the inability to form a pole sheet. Comparing Examples 1-2 with Comparative Examples 2, 4 and 5, it can be seen that compared with the case where no carbon nanotubes are included in the binder (including no carbon nanotubes in the binder and carbon nanotubes in the slurry) and no dispersant in the negative electrode sheet, the negative electrode sheet for lithium batteries of the present invention has improved slurry dispersibility, first discharge capacity, first efficiency and capacity retention rate after cycles. See also Figure 1 ,Depend on Figure 1 It can be seen that in the implementation of directly adding carbon nanotubes to the negative electrode slurry, such as in Comparative Example 4, due to the differences in surface properties between different materials, most carbon nanotubes can only be distributed on the graphite surface and between graphite and amorphous silicon oxide particles, resulting in the inability to fully exert the performance of amorphous silicon oxide materials. In the implementation of adding carbon nanotubes to the binder, such as in Example 1, a conductive binder in which carbon nanotubes are compounded in the binder is used, and the carbon nanotubes can be evenly distributed following the binder, and are distributed on the graphite surface, the amorphous silicon particle surface, and between graphite and amorphous silicon oxide particles, which greatly improves the utilization rate of carbon nanotubes and promotes the improvement of silicon-based material performance. See Figure 2 ,Depend on Figure 2It can be seen that in the embodiment where the negative electrode material uses a conventional PAA binder and does not contain lignin sulfonate, such as Comparative Example 2, a large number of bubbles appear in the slurry coated on the surface of the electrode sheet, resulting in electrode sheet leakage, while in the embodiment where the negative electrode material uses a conductive PAA binder containing carbon nanotubes and sodium lignin sulfonate, such as Example 1, the generation of bubbles is significantly suppressed and no leakage occurs. In addition, by comparing Examples 1-2 with Comparative Examples 3 and 6, it can be seen that the negative electrode sheet having a specific content of carbon nanotubes and dispersant of the present invention has improved slurry dispersibility, first discharge capacity, first efficiency and capacity retention rate after cycling.

[0045] In addition, the negative electrode materials and batteries of Example 3 and Comparative Examples 8-10 were prepared using the same method as Example 1 but with different graphite or silicon dioxide materials, and the first discharge capacity, first efficiency, and capacity retention rate after cycling of the prepared batteries were tested using the same method as above. The test results are shown in Table 2.

[0046] Table 2

[0047]

[0048] Comparing Examples 1 and 3 with Comparative Examples 8-11, it can be seen that when the parameters of graphite and silicon oxide used in the negative electrode material are outside the scope of the present invention, the initial capacity, initial efficiency or capacity retention rate of the battery after cycling will decrease.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A negative electrode sheet for a lithium battery, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode material, wherein the negative electrode material comprises: A negative electrode active material, wherein the negative electrode active material comprises graphite and a silicon-based material; Conductive agent; a binder comprising carbon nanotubes; and The dispersant comprises one or both of lignin sulfonate and humic acid.

2. The negative electrode sheet according to claim 1, characterized in that: The silicon-based material includes one or both of silicon monoxide and silicon-carbon composite materials, preferably amorphous silicon monoxide.

3. The negative electrode sheet according to claim 2, characterized in that: The particle size D of the silicon oxide 50 1μm <D 50 <10μm, of which particles with a diameter of <3μm account for 5%-30%, and the size of the silicon grains in the silicon monoxide is <1nm.

4. The negative electrode sheet according to claim 1, characterized in that: The graphite is selected from natural graphite, artificial graphite or a mixture thereof; the peak intensity ratio D / G of the D peak to the G peak of the Raman spectrum of the graphite is in the range of 0.04-1, preferably 0.3-0.9; and the graphite has a conductivity of >300s / cm, preferably >400s / cm, measured at a pressure of 130MPa according to a four-probe test method.

5. The negative electrode sheet according to claim 1, characterized in that: The conductive agent includes conductive carbon black, conductive graphite, vapor-grown carbon fiber or a combination of two or more thereof. Preferably, based on the total solid weight of the negative electrode material, the amount of the conductive agent in the negative electrode material is 1%-3% by weight.

6. The negative electrode sheet according to claim 1, characterized in that: The binder includes polyvinylidene fluoride, polyacrylic acid, styrene-butadiene rubber, carboxymethyl cellulose binder or a combination of two or more thereof, preferably polyacrylic acid binder; preferably, based on the total solid weight of the negative electrode material, the amount of the binder in the negative electrode material is 2%-4% by weight.

7. The negative electrode sheet according to claim 1, characterized in that: The dispersant comprises lignin sulfonate, preferably sodium lignin sulfonate; preferably, the amount of the dispersant in the negative electrode material is 0.2%-3% by weight based on the total solid weight of the negative electrode material.

8. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: The viscosity of the binder is in the range of 400-30000 mPa.s, preferably 3000-20000 mPa.s.

9. The negative electrode sheet according to any one of claims 1 to 7, characterized in that: Based on the mass of the binder, the content of the carbon nanotubes contained in the binder is 0.01%-1%, preferably 0.02%-0.3%.

10. A lithium-ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 9.